The Effectiveness of Self-Instructional Module on Knowledge Regarding Vitamin D Deficiency Among Women in Selected Institutions, Bangalore - Suhana Job Dondapati; Padmavathi S.; Shiny Chittibabu V.; Leena Raj Pallivela (International Journal of Women's Health Nursing And Practices, 2025)
Background and Purpose of the Study:Vitamin D deficiency is a widespread but often overlooked global health concern, affecting more than one billion individuals worldwide. Insufficient levels of vitamin D have been linked to an elevated risk of developing various chronic illnesses. Objectives: The primary aim of this study was to assess women’s baseline knowledge about vitamin D deficiency. It also sought to evaluate the effectiveness of a self-instructional module (SIM) in enhancing their knowledge by comparing the average pre-test and post-test scores. Additionally, the study examined whether there was any association between pre-test knowledge levels and selected socio-demographic variables. Methods: This quantitative research employed a pre-experimental, one-group pre-test post-test design, involving 60 women. Participants were selected using a non-probability convenience sampling technique. A structured knowledge questionnaire was used to gather data, and participants were provided with a self-instructional module on vitamin D deficiency. Results: The analysis showed that 73.3% of participants had inadequate knowledge in the pre-test. However, following the intervention, 90% demonstrated adequate knowledge in the post-test, indicating a substantial improvement. No significant association was found between pre-test knowledge scores and the socio-demographic variables examined. Conclusion: The findings suggest that the self-instructional module was effective in improving knowledge among women about vitamin D deficiency. A significant difference was observed between the pre-test and post-test knowledge scores, highlighting the usefulness of educational interventions in increasing awareness.
Keywords: Bangalore; Knowledge; Self-instructional module; evaluate; vitamin D deficiency; women